CONTRAST INDUCED NEPHROPATHY IN HIGH RISK PATIENTS - MYTH OR REALITY - Zahid Nabi; Nosheen Anjum; Raja Muhammad Rashid; Zahid ul Zahideen (Journal of Ayub Medical College Abbottabad, 2021)
Background: Contrast induced nephropathy (CIN) is potential stumbling block administration of contrast media. CIN has been defined as as elevation of serum creatinine (sCr) of more than ‰¥0.5 mg/dl (44 Î¼mol/l) or 25% from the baseline within 48-72 hours in the truancy of alternate tenets of acute kidney injury. Incidence of CI-AKI in patients undergoing coronary angiography with normal baseline renal function was reported to be <3%. However, the occurrence of CI-AKI was found to be as high as 50% in CKD patients undergoing Coronary Angiography. This high incidence reported by different studies is mainly because of the difference in definition, underlying renal failure, type and dose of contrast media used and frequency of other co-existing important causes of acute kidney injury (AKI).Recent studies have been published showing that risk of CIN is an overestimated and over-reckoned entity in literature. Objective: To determine the frequency of CIN in CKD patients with Creatinine clearance (Crcl) less than 60 ml/min undergoing contrast exposure. Methods: We conducted Prospective, controlled single center trial in 42 patients having the creatinine clearance of less than 60 ml/min, they were risk stratified according to Mehran scoring system and underwent coronary angiography or contrast enhanced CT scan with contrast and specific protocol for prevention of CIN including intra-venous (IV) hydration with 0.9% Normal Saline was given before the procedure and were followed up to initial 72 hours post procedure. Results: 33 out of 42 patients, i.e., got adequate hydration as per protocol however 11 patients underwent procedure as pre-existing condition did not allow so. Out of 42 patients, risk stratification according to Mehran Scoring system revealed that 15 patients out of 42 patients were included in very high risk group, 14 were in high risk group and 13 patients were in intermediate risk group. Our experience revealed that 5 out of 42 patients (11.3%) were those who experienced CI-AKI and interestingly none of them required haemodialysis. Conclusion: Our study has raised serious question on incidence of CIN in high risk patients as reported previously. However, more studies are needed over this issue till that time we might consider CIN A myth rather than a reality.